Ghost rodents: Albinism in Australian rodent species - Darcy Watchorn; Chris Dickman; Judy Dunlop; Emmalie Sanders; Molly Watchorn; Phoebe Burns (Ecology and Evolution, 2023)
Abstract While almost half of all mammal species are rodents, records of albinism in free‐ranging rodents are very rare. Australia has a large and diverse assemblage of native rodent species, but there are no records of free‐ranging albino rodents in the published literature. In this study, we aim to improve our understanding of the occurrence of albinism in Australian rodent species by collating contemporary and historic records of this condition and providing an estimate of its frequency. We found 23 records of albinism (i.e., a complete loss of pigmentation), representing eight species, in free‐ranging rodents native to Australia, with the frequency of albinism being generally <0.1%. Our findings bring the total number of rodent species in which albinism has been recorded globally to 76. While native Australian species represent only 7.8% of the world's murid rodent diversity, they now account for 42.1% of murid rodent species known to exhibit albinism. We also identified multiple concurrent albino records from a small island population of rakali (Hydromys chrysogaster) and discuss the factors that may contribute to the relatively high frequency (2%) of the condition on this island. We suggest that the small number of native albino rodents recorded in mainland Australia over the last 100 years means that traits associated with the condition are likely deleterious within populations and are thus selected against.